A research agenda for far-right violence and extremism - Gunaratna, Rohan; Pethő-Kiss, Katalin (Elgar research agendas, 2024)
"Elgar Research Agendas outline the future of research in a given area. Leading scholars are given the space to explore their subject in provocative ways, and map out the potential directions of travel. They are relevant but also visionary. This prescient Research Agenda offers an in-depth understanding of the increasing trend of far right-inspired political violence. As domestic extremism becomes a critical priority for governments worldwide, editors Rohan Gunaratna and Katalin Pethö-Kiss scrutinize the threat landscape and analyze far-right groups in countries of the greatest concern. Bringing together an array of esteemed contributors with nation-specific expertise, A Research Agenda for Far-Right Violence and Extremism spans a broad geographic area. It identifies relevant threat indicators and explains the trends and patterns of far right-related extremism and violence. Chapters discuss extremist movements fighting in Ukraine, far right groups of the greatest concern in the UK, the threat landscape in Canada and the mainstreaming of the radical right in the US. Using Bruce Hoffman's assertion that terrorists live in the future, this compelling Research Agenda argues that in order to forecast the forthcoming threat, it is critical to have greater insights into the prevailing assumptions and ambiguities in the present. Incisive and informative, this Research Agenda will be a crucial resource for scholars and researchers specialising in counter-terrorism, the prevention of violent extremism, terrorism and security, international politics and political theory. Its analysis of threat patterns and its global scope will also be of interest to professionals working in both domestic and foreign policy"--